Knowledge on informed consent by in training physicians - Zavala, Salomón (2010)
Objectives: To determine physicians applicants to the medical residency´s knowledge on informed consent. Design: Questionnaire on informed consent. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: Physicians applying to postgraduate medical residency. Methods: A multiple choice examination was elaborated. One thousand four hundred and eighty six (95 %) applicants to the Universidad Nacional Mayor de San Marcos 2009 medical residency participated in the study. An Excel data base was prepared and SPSS 15 for statistic frequency analysis and Atlas-ti for qualitative analysis were used. Participation in the study was voluntary and anonymous. Main outcome measures: Knowledge on informed consent. Results: Fifty-six per cent of participants were male with a mean age of 31.5 (S.D. 5.1) and range between 23 and 58. They graduated in 26 national medical schools and 14 foreign medical schools; one of every three graduated between 2007 and 2008. The majority (84%) answered that to respect patient’s autonomy improves doctor/patient communication; three of every four stated that to obtain informed consent is an ethical imperative. The frequency of correct answers decreased with questions on who establishes the mental capacity and what to do when the patient refuses treatment. Conclusions: The studied population was heterogeneous with regards to age, university of origin and year of graduation. Some deficiencies on knowledge on informed consent were identified.